Handbook of research on mergers and acquisitions (Cheltenham, 2012)
"For the last four decades, researchers in various disciplines have been trying to explain the enduring paradox of the growing activity and volume of mergers and acquisitions (M&A) versus the high failure rate of M&A. This Handbook will stimulate scholars to focus on new research directions. The contributors explore how underlying concepts and methodologies can make an important contribution towards understanding M&A and their performance. This authoritative volume presents research that incorporates multidisciplinary, multi-level, multi-stage and cross-cultural models and analyses, and also focuses on such issues as process-content, knowledge transfer, due diligence, performance measures, communication, trust, grief, integration approaches, individual values, change management, and consulting."